Investigation of Connectedness Effects in the Euro Region: The Case of the Real Estate Prices Index - Öznur Taşdöken; Hakan Kahyaoğlu (İstanbul İktisat Dergisi)
Shocks occurring in the housing market among countries using the common currency in the European Union also cause fluctuations in real estate market prices. Therefore, the analysis of the spread and mutual influence of price fluctuations in the real estate market on the economies of countries becomes essential in the implementation of macroeconomic and common monetary policies. In terms of the social and economic impact of the housing market, this information has become the most important source for understanding countries’ investment preferences and price dynamics. Consequently, what initially begins as country-specific shocks in housing markets often evolves into a structure in which these shocks affect housing markets in other countries. Within this framework, the primary objective of this study is to present findings regarding the estimation of parameters related to the interconnectedness of shocks occurring in the housing markets of countries using the single currency of the European Union with other countries’ housing markets.Otherwise, it explores the macroeconomic impacts of countries’ housing markets in the Eurozone due to the mutual interdependence among these countries.The main findings obtained from the study indicate that shocks in the left tail (τ = 0.05) and right tail (τ = 0.95) have a greater impact on connectivity than shocks obtained from median predictions. This demonstrates that relying solely on median-based predictors is not appropriate for examining return transmissions associated with extreme positive/negative events. This is because shocks in the housing market propagate more strongly in the right and left tails than in the median.